Pertumbuhan dan Produksi Tanaman Cabai Merah Keriting (Capsicum annum L.) Hidroponik terhadap Pemberian Formulasi Nutrisi AB-Mix dan Beberapa Konsentrasi Pupuk Daun - Indrani, Annisa; Hamiranti, Rahmadyah; Ali, Fahri; Tiara, Dede (Politeknik Negeri Lampung, 2024)
This research aims to get the best AB-mix nutritional formulation for growth and production curly red chili plants; to get the best concentration of foliar fertilizer for growth and production of curly red chili plants; to find out interactions between the use of AB-mix nutritional formulation and foliar fertilizer on growth and curly red chili plants. This research uses a split plot consists of 2 factors with 3 replications. The first factor is the AB mix (F) nutritional formulation with 4 levels treatments namely F1 (P 75, K 402, Ca 150, Mg 60, 90 ppm), F2 (P 105, K 432, Ca 180, Mg 90, S 120 ppm), F3 (P 135, K 462, Ca 210, Mg 120, S 150 ppm) and F4 (P 165, K 492, Ca 240, Mg 150, S 180 ppm). The second factor is foliar fertilizer (D) with 3 levels, namely 3, 5 and 7 g.l-¹. The best AB-mix formulation is found in F4 on all observation parameters. The best concentration foliar fertilizer is D3 on the number of main branches, fruit weight planting and number of fruit. There is AB-mix nutritional formulation and Provit maxi Foliar Fertilizer did not produce any significant interactionsreal in all observation parameters.